Land cover change and its eco-environmental responses in Nepal - Li, Ainong; Deng, Wei; Zhao, Wei (Springer, 2017)
This book offers a systematic investigation of the ecological and environmental issues related to the land cover changes in Nepal by researchers from both China and Nepal. It discusses the eco-environmental issues faced by Nepal, particularly in the hills and mountain regions. It also sheds light on the global concerns regarding the eco-environment issues of mountains, and analyzes the various causes and potential consequences of eco-environmental degradation in Nepal. The book is of particular interest to students, researchers, experts, and decision-makers wanting to gain a general overview of land cover in Nepal and its dynamics, environment and natural resources, as well as mountain hazards.
Keywords: Land use -- Nepal.; Land cover -- Nepal.; Nepal.; elektronické knihy; electronic books